Perspectives on Consumer Choice From Behavior to Action, from Action to Agency - Foxall, Gordon R. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Evaluating the ways in which we construe consumer choice, this book examines the psychology, methods and realities of the role it plays for today's consumer. Confronted by competing brands and products, services, and e-tailed opportunities that are but a click away, how does the consumer choose among them to achieve the particular array of goods to suit their lifestyle? Consumer researchers often seek to explain consumer choice by attributing it to beliefs, desires, attitudes, and intentions in the absence of any theoretical justification. Perspectives on Consumer Choice is the outcome of a research program that employs cognitive explanations in a responsible and disciplined way to genuinely elucidate consumer choice in social scientific terms. Employing a reasoned approach to understanding consumption, this book builds upon theoretical and empirical research in economic psychology, behavioral economics and philosophy as well as marketing and consumer research. .